Telegestión del alumbrado público con tecnología LED. Estudio de un plan piloto para la Avenida Pio Jaramillo Alvarado de la ciudad de Loja. - González Loaiza, Pablo David (2014)
This thesis is aimed at enhancing energy efficiency in public lighting systems by projecting a pilot program of remote management of street lighting with LED technology on Pio Jaramillo Alvarado Avenue in the city of Loja. Initially a general analysis of public lighting is set in the area of study to define the current status of the zone, and identify the potential methods of efficiency savings. Subsequently, by studying all the variables that constitute a lighting system, a solution of remote management and LED lighting is set, a simulation of technology replacement is performed and finally a economic and technical comparison between the current lighting system and the projected system is made. The public lighting system of the Avenida Pio Jaramillo Alvarado is currently composed of 183 luminaries high-pressure sodium whose annual consumption of energy is 319,446.54 kWh. Through the initial diagnosis was determined that depending on the lighting parameters established in the regulatory standard, the system does not meet with the variables of illuminance and uniformity in both the road surfaces, such as in roundels, evidencing a low quality in the provision of the service. In this study raises the replacement of all the luminaires for sodium by LED luminaires, complemented by the inclusion of a model of remote control to regulate the functioning of the system studied. The resulting reduction in electrical consumption to 105,162.05 kWh per year, equivalent to a saving of approximately 67.08 % and in addition a significant decrease in maintenance costs. This replacement technology is based on the simulation using the DiaLux software in where it was determined that with the luminaires can be selected to meet the demands required lighting and improving the current conditions of the system. The benefits of the planned system determine an improvement in the energy rating system, which on average goes from category C of the lighting system to the current category in the projected coordinate system. In addition it predicts a positive environmental impact, mainly because thanks to the alternatives raised would no longer be issuing 62.14 tonnes of CO2 per year.